SOUND CHANGES IN MANUSCRIPTS OF OLD UZBEK WRITING - Kumushoy Shavkatova; Nafisa Muratova (European Science Publishing, 2024)
This article talks about sound changes in old Uzbek manuscripts. It is analyzed based on conversion. The letters in the manuscript sources were analyzed by comparing them with other letters.
Keywords: changes, assimilation, accommodation, pracopa, falling sound, rising sound.